CORPORATE GOVERNANCE IN PT. BANK MANDIRI (PERSERO) TBK - Winardi, Wasis (Dinasti Publisher, 2020)
Good Corporate Governance is now very important to increase the trust of investors and shareholders of the company. In fact, many companies make Good Corporate Governance (GCG) one of the company's strategies to achieve goals optimally, even used as a measurement tool to assess the quality of the company's work structure. Good corporate governance shows that all parties responsible for the business continuity of the company have understood and played a good role in carrying out their duties and responsibilities in accordance with their authority. Careless management of a company is not only detrimental to shareholders, but also threatens the survival of the company itself. Having ambitious attitudes to achieve business targets is certainly important for management, but excessive ambition can result in companies violating business ethics, internal / external provisions, and even breaking the law. The research method used for writing this article is the Qualitative Descriptive method with the study of literature relating to Corporate Governance; writing is done in a structured manner, according to the facts and field conditions of the research object. The author describes the conditions in accordance with the data, the results of the analysis and interpretation of the theories and applicable provisions. The purpose of this study was to determine how well the implementation of Good Corporate Governance in PT. Bank Mandir (Persero) Tbk.